DETEKTIF kepo / gambar, Hendhy...[et.al]; cerita, Al Mujahidatul Adilah...[et.al]; penyunting ilustrasi, Rony Amdani; penyunting naskah, Wiwit Wijiastuti - Hendhy; Al Mujahidatul Adilah; Rony Amdani; Wiwit Wijiastuti (Muffin Graphics, 2016)
95 hlm. : ilus. ; 21 cm.